Ultrasound-guided Needle nerve contact positions detection in Regional Anaesthesia using Needle tip force and Opening injection pressure. (May 2020) - Zhang, Shengli; Graeme,; George,; Qiao, Panpan; Huang, Zhihong; Xia, Chunming
Abstract: Ultrasound imaging guidance has been widely used in peripheral nerve block to guide the anaesthetist to insert the needle and observe injection fluid diffusion. However, needle-nerve contact(NNC) positions visualization is difficult to achieve because of requirement of high image solution and expert. To better guide the anaesthetist to predict the distance from needle to nerve and reduce the needle trauma, we attempted to use Needle tip force(NTF) and Opening injection pressure (OIP) to identify the NNC positions under ultrasound guidance. The relationship between OIP and NNC, NTF and NNC, NTF and OIP is unclear now, and we conducted a prospective, observational study to define the relationship. In this study, we designed a multi-function block needle and built a real-time NTF and OIP measurement which could trace and record NTF and OIP data in the simulator sciatic nerve. NNC positions were divided into three distinct NNC positions: Pre-NNC, First-NNC, Forceful-NNC using ultrasound guidance image. We statistically analysis NTF, OIP in the three NNC positions, and the results indicate the NTF differentiate in three NNC positions(p<0.001), OIP differentiate as well (p<0.001) and the NTF has a highly positive with the OIP in the same NNC positions with Pearson correlation 0.62.